2010
DOI: 10.1002/wsbm.85
|View full text |Cite
|
Sign up to set email alerts
|

Odor representations in the mammalian olfactory bulb

Abstract: A first key step in studying a sensory modality is to define how the brain represents the features of the sensory stimulus. This has proven to be a challenge in olfaction, where even the stimulus features have been a matter of considerable debate. In this review, we focus on olfactory representations in the first stage of the olfactory pathway, the olfactory bulb (OB). We examine the diverging viewpoints on spatially organized versus distributed representations. We then consider how odor sampling through respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…For interpretation of these maps, please note that patterns are bilaterally symmetric across a tilted axis around the horizontal midline (cf. Khan et al, 2010). For anatomic terms of location, please refer to Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…For interpretation of these maps, please note that patterns are bilaterally symmetric across a tilted axis around the horizontal midline (cf. Khan et al, 2010). For anatomic terms of location, please refer to Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…We chose to simulate variations in odor intensity by MC spike phase locking, which seems to be one of the critical parameters varying with intensity ( Margrie and Schaefer, 2003 ; Courtiol et al, 2011a ; Fukunaga et al, 2012 ), as it also increases the chance of MCs and GCs to fire together during the respiratory cycle. Other MC response parameters that were shown experimentally to vary with odor intensity, such as the firing rate or the number of activated glomeruli, as has been reported in many studies ( Meister and Bonhoeffer, 2001 ; Khan et al, 2010 ), were not directly studied here. Although the influence of the above parameters could explain the decrease in gamma oscillations, as reported in Figure 2 , they cannot by themselves only explain the experimentally observed increase of the beta oscillations because the phase dispersion of MC firing is the critical parameter in our model for the emergence of beta oscillation.…”
Section: Discussionmentioning
confidence: 99%
“…This cascade of events, could, in turn, contribute to the neural representation of elevated odor intensity. Higher concentration of odors activate additional, lower affinity ORs at the olfactory epithelium, resulting in more glomerular activations in the olfactory bulb (Fried et al, 2002;Khan et al, 2010). These additionally recruited, low-affinity ORs may drive differences in odor quality and perceived intensity by modulating neuronal firing in higher olfactory areas (Stettler and Axel, 2009).…”
Section: Or Populations Encoding Odor Concentrationsmentioning
confidence: 99%
“…Odorants are represented by combinatorial codes whereby a given odorant, at a specific concentration activates a specific combination of ORs, which in turn activate a specific combination of glomeruli (Malnic et al, 1999;Rubin and Katz, 1999;Bozza et al, 2002;Oka et al, 2006;Saito et al, 2009). Previous studies found an increase in the recruitment of active ORs (in the OSNs) and glomeruli (in the olfactory bulb) in response to higher odorant concentrations (Rubin and Katz, 1999;Fried et al, 2002;Khan et al, 2010;Jiang et al, 2015;Wilson et al, 2017). There is, however, insufficient research determining the identity of these ORs and their collective responses at different odorant concentrations in vivo.…”
Section: Introductionmentioning
confidence: 99%